Sintering of zirconia composites obtained by slip casting - dos Santos, IMG; Moreira, RCM; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2001)
Composites containing a matrix of nanometric Ce-stabilized zirconia with an addition of micrometric monoclinic zirconia were processed by slip casting and sintered at a relatively low temperature. The ratio between nanometric and micrometric particles was determined according to the viscosity of the suspensions and the final density of the pellets. An optimum amount of micrometric particles was necessary to achieve improved suspension dispersion and higher pellet density. The amount of deflocculant in the suspensions containing the mixture of micrometric and nanometric particles was optimized by viscosity measurements. The pellets were characterized by dilatometry, Hg porosimetry, density measurement (the Archimedes method) and scanning electron microscopy. Despite the low green density obtained (35-38% of the theoretical density), densities as high as 97.5% were achieved after sintering. (C) 2001 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: slip casting; sintering; ZrO2; nanometric particles